Pedestrian Evacuation Modelling with Dynamics Congestion Avoidance - Wang, Zongzhi; Chen, Tao (Collective Dynamics, 2020)
With the development of computer technology, pedestrian simulation becomes an efficient method to analyse evacuation efficiency under various scenarios. Some important and common behaviour of pedestrians, congestion detection and avoidance, which is seldom considered in pedestrian simulation complicatedly, are discussed in this paper. A modified cellular automata model considering dynamic congestion detection and avoidance is proposed and applied to simulate two different scenarios to demonstrate the effect of congestion avoidance behaviour, which have a significant improvement on evacuation efficiency. The accuracy and efficacy of this model is verified through the comparison result which is conducted through commercial software, Pathfinder. The modified model shows that with the consideration of congestion avoidance behaviour properly, the evacuation efficiency is improved approximately 40% than the model proposed by this paper, without the consideration of congestion avoidance behaviour.